RESCHEDULLING PROYEK PERKUATAN STRUKTUR DERGAMA BERLIAN TANJUNG PERAK SURABAYA MENGGUNAKAN MICROSOFT PROJECT - Mohammad Rizal Mantovani Rizal (Departement of Civil Engineering, Universitas Winaya Mukti, 2023)
In the implementation of a project sometimes it does not go well, because there are obstacles that hinder the existing work. One of the obstacles that are often encountered in the field in the Tanjung Perak Diamond Pier Structure Strengthening project in Surabaya is uncertain weather conditions, this is because in carrying out the initial planning the planners did not consider the weather conditions that would occur during the implementation of this project. The impact that arises due to this delay is the increase in the duration and budget for the implementation of the project. So that in overcoming this, rescheduling is carried out which is expected to produce a logical and realistic schedule. Many methods are used in scheduling, where the method is expected to facilitate planning scheduling. The purpose of this research is to calculate the required duration of the project implementation after rescheduling. This type of research is analytic in nature. Data collection in the form of secondary data such as schedules and Budget Plans (RAB) is carried out by directly requesting the required data from related parties, then evaluating the initial schedule, followed by preparing a new schedule using Microsoft Project tools using the Critical Path Method (CPM) ). The results of this study showed that the duration of rescheduling was 99 days, 22 days faster than the actual planned duration of 121 days. Keywords : Reschedulling, RAB, Microsoft Project